THE EFFECT OF FACILITIES ON CUSTOMER SATISFACTION AT SATRIA FUTSAL NATAR DISTRICT - Miranda Ariyanti; Vonny Tiara Narundana (ZILLZELL MEDIA PRIMA, 2025)
This study aims to find out about the significant influence of facilities on customer satisfaction. The researcher implemented a quantitative type method with 200 populations and 133 samples obtained through the Purposive Sampling Technique. The researcher used a simple linear regression test using a hypothesis test, namely the t-test. This research results in a positive influence of facilities on customer satisfaction. Furthermore, with the overall influence of facilities on customer satisfaction, which is 68% while the remaining 32% is influenced by other variables. If the service business, especially Satria Futsal, pays attention to both the completeness and comfort of the facilities directly and indirectly, then this can cause a sense of satisfaction from customers.